(untitled) (Research, Society and Development, 2020)
The conoid teeth are anomalies of size and shape changing the harmony of smile, may affect self-esteem of the patients. The aim of this case report was describe a reanatomization of conoid teeth in a patient with epilepsy and mental deficit. A sixteen- years-old boy presented to Department of Pediatric Dentistry and Orthodontics at the Federal University of Rio de Janeiro, the with chief complaint of poor dental aesthetic due to small teeth. During the anamnesis, the upper lateral incisors showed reduced size and conoid shape, diastemas and harmful smile harmony. Therefore, the clinical conduct was performed with the aim of restore the self-esteem and allows a harmonic smile, by means of reshape with indirect composite resin.